2010
DOI: 10.1002/nme.2887
|View full text |Cite
|
Sign up to set email alerts
|

Limit analysis of plates and slabs using a meshless equilibrium formulation

Abstract: Published paperLe, Canh V., Gilbert, Matthew and Askes, Harm (2010) SUMMARYA meshless Element-Free Galerkin (EFG) equilibrium formulation is proposed to compute the limit loads which can be sustained by plates and slabs. In the formulation pure moment fields are approximated using a moving least squares technique, which means that the resulting fields are smooth over the entire problem domain. There is therefore no need to enforce continuity conditions at interfaces within the problem domain, which would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 29 publications
(54 reference statements)
0
24
0
Order By: Relevance
“…where r and  are local crack tip polar coordinates, taking account for the first term concerning with the SIF in crack tip asymptotic displacement fields (Le et al, 2010;Fries & Belytschko, 2010). Enriched nodes near a crack tip could be chosen by various ways.…”
Section: Xfem For Linear Elastic Crackmentioning
confidence: 99%
See 2 more Smart Citations
“…where r and  are local crack tip polar coordinates, taking account for the first term concerning with the SIF in crack tip asymptotic displacement fields (Le et al, 2010;Fries & Belytschko, 2010). Enriched nodes near a crack tip could be chosen by various ways.…”
Section: Xfem For Linear Elastic Crackmentioning
confidence: 99%
“…Enriched nodes near a crack tip could be chosen by various ways. First, only elements containing a crack tip are completely enriched with singular functions (Le et al, 2010). With this technique, one or more layers of neighboring elements are added to the enriched region, so that its size is increased.…”
Section: Xfem For Linear Elastic Crackmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [4] also applied the element-free Galerkin method to the lower bound shakedown analysis of structures under variable repeating loads. Le et al [5,6] used element-free Galerkin method to discretize the moment eld in the limit analysis of plates. Liu and Zhao [7] used the radial point interpolation method and nonlinear programming to develop a technique for upper bound limit analysis of solid structures.…”
Section: Introductionmentioning
confidence: 99%
“…It is known as the stabilized conforming nodal integration (SCNI) scheme. The SCNI scheme has been applied successfully to various problems, for instance, elastic analysis [12][13][14], plastic limit analysis [15], error estimation [16] and a stabilized mesh-free equilibrium model for limit analysis [17]. It is shown that, when the SCNI scheme is applied, the solutions obtained are accurate and stable, and locking problems can also be prevented.…”
Section: Introductionmentioning
confidence: 99%